x(x+4)=-84

Simple and best practice solution for x(x+4)=-84 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+4)=-84 equation:


Simplifying
x(x + 4) = -84

Reorder the terms:
x(4 + x) = -84
(4 * x + x * x) = -84
(4x + x2) = -84

Solving
4x + x2 = -84

Solving for variable 'x'.

Reorder the terms:
84 + 4x + x2 = -84 + 84

Combine like terms: -84 + 84 = 0
84 + 4x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-84' to each side of the equation.
84 + 4x + -84 + x2 = 0 + -84

Reorder the terms:
84 + -84 + 4x + x2 = 0 + -84

Combine like terms: 84 + -84 = 0
0 + 4x + x2 = 0 + -84
4x + x2 = 0 + -84

Combine like terms: 0 + -84 = -84
4x + x2 = -84

The x term is 4x.  Take half its coefficient (2).
Square it (4) and add it to both sides.

Add '4' to each side of the equation.
4x + 4 + x2 = -84 + 4

Reorder the terms:
4 + 4x + x2 = -84 + 4

Combine like terms: -84 + 4 = -80
4 + 4x + x2 = -80

Factor a perfect square on the left side:
(x + 2)(x + 2) = -80

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 7x^2-36x+6=0 | | 3x(x-1)+15=7 | | 40+2y-16=11y-11-4y | | 1223423123x=213123123 | | -3x+18=-10x+4 | | 3x+9=5x-19 | | 6(2.5)+3y=12 | | (3x)(3x-2)(x)=540 | | 0=0.3x^2+2x-50 | | x-55=10 | | 2q^3-5q^2-500=0 | | 42-n*n=n | | 1996+43x=0 | | log(10)x+log(10)x-1=log(10)30 | | -24+11=5x+3-4x | | .10(c+3)=-12 | | log(x)+log(x-1)=log(30) | | 21-x=28 | | n-n*n=72 | | 4(a+9)=7[a-(3-a)] | | 9x^2=50x-25 | | 4x-7=36 | | x^3-5x^2+4x-2=0 | | 42x=35x+70 | | 6(4n-4)=-60 | | 8-2n=40 | | 7x+7=-5x+43 | | 49s^2-14s+1=0 | | 8k^2-20=-9k | | 5(7+2)=x-11 | | x-0.4=4.2 | | f(x)=ln(6x) |

Equations solver categories